Intracoronary Versus Intravenous Adenosine-Induced Maximal Coronary Hyperemia for Fractional Flow Reserve Measurements - Khashaba, Ahmed (Libertas Academica, 2014)
BACKGROUND: Maximal hyperemia is the critical prerequisite for fractional flow reserve (FFR) assessment. Despite intravenous (IV) adenosine currently being the recommended approach, intracoronary (IC) administration of adenosine constitutes a valuable alternative in everyday practice. However, it is surprisingly unclear which IC strategy allows the achievement of FFR values that are comparable to IV adenosine. OBJECTIVES: This study sought to compare increasing doses of IC adenosine versus IV adenosine for FFR. METHODS: 30 intermediate coronary stenoses undergoing FFR measurement were prospectively and consecutively enrolled. Hyperemia was sequentially induced by bolus of IC adenosine (ADN; 150 μg) followed by IV adenosine (IVADN) infusion over 3 minutes at dose of (140 μg/kg/min). FFR values, symptoms, and development of atrioventricular block were recorded. RESULTS: 150 μg doses of IC adenosine were well tolerated and associated with fewer symptoms than IV adenosine. Intracoronary adenosine doses induced a significant decrease of FFR compared with baseline levels (P < 0.01). Among the 6 patients with FFR values less than 0.80 identified by IVADN, 4 were correctly identified also by 150 μg bolus IC adenosine. Larger randomized studies with cross-over design are necessary to verify the results. CONCLUSIONS: This small pilot study suggests that IC adenosine might be an alternative to IV adenosine. Larger randomized studies with a cross-over design are necessary.